Rancang Bangun Sistem Informasi Penjualan Kemeja Berbahan Flanel Berbasis Web - Eko Setia Budi; Yamin Nuryamin (Journal of Computer System and Informatics (JoSYC), 2020)
Along with the development of the technology world, especially the internet where the availability of various kinds of information can be obtained easily, making almost every activity carried out through internet media starting from getting information, looking for news, communication facilities, promotions, buying and selling activities, and so forth. This also prompted the writer to create and design information system for selling web-based flannel shirts, where the web was specifically used for fasion fans, especially fans of flannel shirts. With the existence of a web like this the author hopes to provide convenience in making purchases and search for the desired product. by displaying various types of flannel shirt products and the ease in the purchase process, it is expected that the web will become one of the online stores that can grow.